1990
DOI: 10.1002/zoo.1430090303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of black‐footed ferret (Mustela nigripes) and domestic ferret (M. putorius furo) courtship activity

Abstract: Because of the scarcity of the endangered black-footed ferret (Mustela nigripes) and the amount of knowledge necessary for their conservation, surrogate research can play an important role in recovery. In this paper, we investigate surrogate behavioral research potential by comparing courtship behavior of the black-footed ferret to the congeneric domestic ferret ( M . putorius furo). Ten female domestic ferrets were bred to five male domestic ferrets and eight female black-footed ferrets were bred to five blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Mating behavior in the black-footed ferret is similar to that of the European ferret (Mustela putorius) and the Siberian polecat (Mustela eversmanni) [Hillman and Carpenter, 1983;Miller et al, 1988;Miller and Anderson, 1990]. Intromission is preceded by specific male behaviors including neck-biting, mounting, and rapid pelvic thrusting that subside after penetration has occurred [Hillman and Carpenter, 1983;Miller and Anderson, 1989].…”
Section: Discussionmentioning
confidence: 75%
“…Mating behavior in the black-footed ferret is similar to that of the European ferret (Mustela putorius) and the Siberian polecat (Mustela eversmanni) [Hillman and Carpenter, 1983;Miller et al, 1988;Miller and Anderson, 1990]. Intromission is preceded by specific male behaviors including neck-biting, mounting, and rapid pelvic thrusting that subside after penetration has occurred [Hillman and Carpenter, 1983;Miller and Anderson, 1989].…”
Section: Discussionmentioning
confidence: 75%
“…This approach was deemed appropriate, because early molecular analyses revealed that the common ferret, Siberian polecat, and black-footed ferret were phylogenetically related [51]. Others had determined that all of these species were seasonal, 'long-day' breeders [100][101][102][103] with increases in testis size beginning in January and peaking from March through June with declines thereafter [104]. The breeding season for the female had been determined to be restricted to March through June and characterized by changes in vaginal cytology and increased vulvar size.…”
Section: Developing Assisted Reproduction Via Studying Ferret 'Models'mentioning
confidence: 99%
“…To this end, reproduction and disease prevention were rigorously tracked and studied. Studies have investigated genetic diversity [ 31 ], courtship [ 32 ], age-dependent male fertility [ 33 ], canine distemper [ 34 , 35 , 36 ] and sylvatic plague [ 37 , 38 , 39 ]. This research was critical to black-footed ferret recovery and reintroduction, but further research into other areas of health, including captivity’s effect on cranial morphology studied here, will serve to continue to improve the conservation efforts of this species.…”
Section: Introdutionmentioning
confidence: 99%